Circular dichroism of chiral Majorana states - Osca, Javier; Serra, Llorenç (Beilstein Journal of Nanotechnology, 2018)
Background: Majorana states in condensed matter devices may be of a localized nature, such as in hybrid semiconductor/superconductor nanowires, or chirally propagating along the edges such as in hybrid 2D quantum-anomalous Hall/superconductor structures.Results: We calculate the circular dichroism due to chiral Majorana states in a hybrid structure made of a quantum-anomalous Hall insulator and a superconductor. The optical absorption of chiral Majorana states is characterized by equally spaced absorption peaks of both positive and negative dichroism. In the limit of a very long structure (a 2D ribbon) peaks of a single sign are favored.Conclusion: Circular-dichroism spectroscopy of chiral Majorana states is suggested as a relevant probe for these peculiar states of topological matter.
Keywords: chiral states; circular dichroism; Majorana modes; optical absorption; topological matter

(untitled) - Nayak, C.; Simon, S. H.; Stern, A.; Freedman, M.; Das Sarma, S. (Rev. Mod. Phys., 2008)

(untitled) - Alicea, J.; Oreg, Y.; Refael, G.; von Oppen, F.; Fisher, M. P. A. (Nat. Phys., 2011)

(untitled) - Stanescu, T. D.; Tewari, S. (J. Phys.: Condens. Matter, 2013)

(untitled) - Beenakker, C. W. J. (Annu. Rev. Condens. Matter Phys., 2013)

(untitled) - Franz, M. (Nat. Nanotechnol., 2013)

(untitled) - Elliott, S. R.; Franz, M. (Rev. Mod. Phys., 2015)

(untitled) - Aguado, R. (Riv. Nuovo Cimento Soc. Ital. Fis., 2017)

(untitled) - Lutchyn, R. M.; Bakkers, E. P. A. M.; Kouwenhoven, L. P.; Krogstrup, P.; Marcus, C. M.; Oreg, Y. (ArXiv, 2017)

(untitled) - Lutchyn, R. M.; Sau, J. D.; Das Sarma, S. (Phys. Rev. Lett., 2010)

(untitled) - Oreg, Y.; Refael, G.; von Oppen, F. (Phys. Rev. Lett., 2010)

(untitled) - Mourik, V.; Zuo, K.; Frolov, S. M.; Plissard, S. R.; Bakkers, E. P. A. M.; Kouwenhoven, L. P. (Science, 2012)

(untitled) - Gül, Ö.; Zhang, H.; Bommer, J. D. S.; de Moor, M. W. A.; Car, D.; Plissard, S. R.; Bakkers, E. P. A. M.; Geresdi, A.; Watanabe, K.; Taniguchi, T.; Kouwenhoven, L. P. (Nat. Nanotechnol., 2018)

(untitled) - Deng, M. T.; Yu, C. L.; Huang, G. Y.; Larsson, M.; Caroff, P.; Xu, H. Q. (Nano Lett., 2012)

(untitled) - Das, A.; Ronen, Y.; Most, Y.; Oreg, Y.; Heiblum, M.; Shtrikman, H. (Nat. Phys., 2012)

(untitled) - Zhang, H.; Liu, C.-X.; Gazibegovic, S.; Xu, D.; Logan, J. A.; Wang, G.; van Loo, N.; Bommer, J. D. S.; de Moor, M. W. A.; Car, D.; het Veld, R. L. M. O.; van Veldhoven, P. J.; et al. (ArXiv, 2017)

(untitled) - Alicea, J. (Rep. Prog. Phys., 2012)

(untitled) - He, Q. L.; Pan, L.; Stern, A. L.; Burks, E. C.; Che, X.; Yin, G.; Wang, J.; Lian, B.; Zhou, Q.; Choi, E. S.; Murata, K.; Kou, X.; et al. (Science, 2017)

(untitled) - Qi, X.-L.; Hughes, T. L.; Zhang, S.-C. (Phys. Rev. B, 2010)

(untitled) - Chung, S. B.; Qi, X.-L.; Maciejko, J.; Zhang, S.-C. (Phys. Rev. B, 2011)

(untitled) - Wang, J.; Zhou, Q.; Lian, B.; Zhang, S.-C. (Phys. Rev. B, 2015)

(untitled) - Lian, B.; Wang, J.; Zhang, S.-C. (Phys. Rev. B, 2016)

(untitled) - Kaladzhyan, V.; Despres, J.; Mandal, I.; Bena, C. (Eur. Phys. J. B, 2017)

(untitled) - Eisfeld, A.; Kniprath, R.; Briggs, J. S. (J. Chem. Phys., 2007)

(untitled) - Longhi, G.; Castiglioni, E.; Koshoubu, J.; Mazzeo, G.; Abbate, S. (Chirality, 2016)

(untitled) - Ruiz, D.; Osca, J.; Serra, L. (J. Phys.: Condens. Matter, 2015)

(untitled) - Osca, J.; Serra, L. (Phys. Status Solidi C, 2015)

(untitled) - Dartiailh, M. C.; Kontos, T.; Douçot, B.; Cottet, A. (Phys. Rev. Lett., 2017)

(untitled) - Olson, J.; Dominguez-Medina, S.; Hoggard, A.; Wang, L.-Y.; Chang, W.-S.; Link, S. (Chem. Soc. Rev., 2015)

(untitled) - Baida, H.; Billaud, P.; Marhaba, S.; Christofilos, D.; Cottancin, E.; Crut, A.; Lermé, J.; Maioli, P.; Pellarin, M.; Broyer, M.; Del Fatti, N.; Vallée, F.; et al. (Nano Lett., 2009)